THE LEADERSHIP OF THE SCHOOL PRINCIPAL IN IMPROVING THE PERFORMANCE OF PRIVATE JUNIOR HIGH SCHOOL NAHDLATUL ULAMA MEDAN - M. Azril (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
The types of head leadership schools in improving teacher performance in Nahdlatul Ulama Private Middle Schools use a variety of participative and situational democratic leadership. The production of teachers in the teaching and learning process in Nahdlatul Ulama Private Middle Schools teaching and learning process is an effort that must be fostered to develop an awareness of the work of teachers about the tasks and responsibilities the answer. The role of the principal's leadership is a crucial element in managing the progression of an institution or school. The principal acts as a catalyst in the sense of being able to inspire and drive the enthusiasm of teachers, staff, and students in achieving the goals that set